(untitled) (Research, Society and Development, 2021)
Society has always been linked to the culture of sexist dominance and women’s memorization, where often, men’s aggressive and sexual drives are satiated using violence and aggression in the intra-family environment. the role of the psychologist in relation to women victims of domestic violence. The present study was a bibliographic research of the integrative literature review type. As for the results, Studies have shown that domestic violence harms the reproductive, physical, especially emotional and mental health of women, where understanding the phenomenon is necessary for the integral monitoring of women, especially psychological. The stigma and fear of being judged mobilize feelings of persecution and make victims consider their social environment as accusatory, as if society were to blame them for the violence they suffered, as a result, some women believe they are responsible for the violence and believe they could have avoided it. It is concluded that this study allowed us to know more about the role of psychologists and assistance to women victims of domestic violence and their interventions, with the aim of preventing or eliminating the symptoms and promoting the victim’s reintegration into society. encourage victims to ask for help in advance, before the situation escalates, resulting in physical violence.